Arabic loan words in English - Asqarova Komila Ergashevna (Zien Journals, 2022)
In this article we are going to analyze English loan words from Arabic language. It begins with different views on Arabic loan words in English from both points of views the English and the Arab linguists. After then, there is a historical preview from the early loaning the first Arabic words in English till the early modern English. Finally, there is a recommendation followed by a conclusion.
Keywords: English; words; Arabic; different